Associations between nonrestorative sleep and suicidal ideation: a Japanese general population survey - Kouju Yamada; Yoshiyuki Kaneko; Chisato Konno; Ryuji Furihata; Yuichiro Otsuka; Yoshitaka Kaneita; Makoto Uchiyama; Masahiro Suzuki (Scientific Reports)
Abstract Insomnia symptoms and short sleep duration are known to be associated with suicidal ideation. The aim of this study was to investigate the association between nonrestorative sleep (NRS), a subjective experience of feeling unrefreshed after waking up, and suicidal ideation in the general population. We analyzed data from a cross-sectional survey of 2559 randomly sampled adults living in Japan. The participants were asked about insomnia symptoms (difficulty initiating sleep, difficulty maintaining sleep, and early morning awakening), NRS, sleep duration, and the presence of suicidal ideation. Logistic regression analysis was used to examine the associations among short sleep duration (< 6 h), insomnia symptoms, NRS, and suicidal ideation. Possible confounding factors were adjusted using propensity scores. In the multivariate analysis adjusting for the confounding effects of other sleep-related factors, in addition to psychiatric, sociodemographic, and lifestyle factors, only NRS showed a positive association with suicidal ideation (adjusted odds ratio [aOR] = 2.266). These findings suggest the importance of focusing on NRS for suicide prevention in the general population.